Analysis of patient satisfaction with the quality of patient service quality in RSUD X in Lampung City - Apriana, Renatd; Meilani, Yohana Cahya F. Palupi (Institute of Computer Science (IOCS), 2023)
This study aims to test and analyze the effect of Ptient Satisfaction with the quality of Patient Service in RSUD X Lampung City by looking at the 5 dimensions of health service quality by distributing questionnaires to 30 samples. This research is a quantitative study which uses the status of people who have completed the administration by using a purposive sampling technique. The quality of patient service by doctors at RSUD X in Lampung city has used a service marketing view, namely service quality whose main concern is the speed of patient handling by doctors. The quality of hospital services has shown services that can be accepted by patients. With the level of patient satisfaction with the doctor, the hospital image will appear after the hospital carries out its activities or performs its services, and this service is felt by the patient.